Knee Pain: Prevention and Treatment - Taylor, J. (Peak Performance, 2007)
Injury briefing l: Meniscal tears Clicking, locking, giving way, pain on bending… sounds like another case of torn cartilage (Sam Oussedik & Fares Haddad) Injury briefing ll: Patellar tendinopathy It is common,obstinate and a real pain in the front of the knee (Malcolm Davies & Fares Haddad) Injury briefing lll: PCL damage The lesser knowncruciate ligament may not be as painful when injured, but that`s no reason to ignore it (Simon Ball & Fares Haddad, Ryan Shulman (case study)) Surgical update l: ACL reconstruction For some athletes a new ACL repair technique sounds promising. And further advances are on the horizon (Matthew Dodd, Sam Oussedik & Fares Haddad) Surgical update ll: Articular cartilage repair Here`s another bit of joint damage to worry about: the ends of bones. And here`s how they can be repaired (Sam Oussedik & Fares Haddad) Surgical update lll: Joint replacement Can a new knee propel your sporting career into old age? (Diane Back & Angus Lewis) The knee in context: two case studies The cases of the footballer and the runner reveal how the source of pain is not always the cause of the problem (Cameron Reid (the footballer), Sean Fyfe (the runner)) Supplements: Glucosamine You`ll never hear a bad word about glucosamine, but here is the hard evidence on whether it works for knee pain (Diane Back) Research round-up: What the sports scientists have been discovering recently about knees - and what our own expert makes of their findings (Nick Grantham) Self-help rehab: The ultimate guide to understanding and fixing your own niggling knee injuries (Cate Streeten)